Efektivitas Model Pembelajaran Project-Based Learning Terintegrasi STEM dalam Peningkatan Kemampuan Literasi Sains Peserta Didik Sekolah Dasar - Telaumbanua, Elisabet Indahsari; Tanjung, Risdanur Fitra Aulia; Aljeffry, Silmi Trirana; Laoli, Hezti Nova Yakin; Tafonao, Nelvis; Gulo, Super Damai Prima; Zega, Yaskarya; Telaumbanua, Natanael Yamohaga; Harefa, Edward (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to see the effectiveness of STEM-based PjBL in increasing the science literacy skills of grade IV elementary school students of SDN 075018 Afilaza which totals 52 people. The method used is a quantitative method in the form of an experiment with a Control Growth Pretest-Posttest Design, where there is an experimental group given the PjBL learning model and a control group given a conventional learning model. The data collection technique uses a science literacy test. The data obtained were analyzed using a t-test. The results of this study show that there is an influence of the PjBL learning model on the improvement of science literacy skills, which can be seen from Sig (0.04) < 0.05 and t-count (2.114) > t-table (2.00758) which states that H0 is rejected and H1 is accepted. Based on the N-Gain results, it shows an increase because the N-Gain result of the control group is 0.34 and the N-Gain result of the experimental group is 0.76